Efektivitas Komunikasi Pemasaran Benih Padi Produksi Koperasi KUAT Subak Guama - I GEDE WEDA WIRTAWAN; I DEWA PUTU OKA SUARDI; I MADE SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Effectiveness of Marketing Communication for KUAT Cooperative Production of Rice Seedsat Subak of Guama KUAT Cooperative of Guama Subak manages a business unit carried out by Subak ofGuama, one of which is an effort to breed rice seeds. The purpose of this research is todetermine the communication competencies of the marketing officer of the KUATCooperative of Guama Subak so that the seeds produced can be sold very well and tofind out how effective the marketing communication of the KUAT Cooperative ofGuama Subak is on rice seed products.Communication is said to be effective if there arecognitive, affective, and conative indicators. The study took place in the KUATCooperative, Subak of Guama, Marga Sub-District, Tabanan Regency. The purpose ofthis study was to determine the communication competencies of marketing officers anddetermine the effectiveness of rice seed marketing communications carried out byKUAT Cooperative of Subak of Guama. The method used is a qualitative descriptiveanalysis method. Based on the results of the study, the communication competence ofthe KUAT rice seed marketing officer of Guama Subak was classified as highlycompetent with an average score of 23.37. The effectiveness of marketingcommunication is categorized as very effective with an average score of 77.3. Theeffectiveness of communication is shown cognitive indicators, consumers know thecharacteristics of rice seeds. Affective indicators, consumers are happy and interested inrice seeds and conative indicators, consumers decide to buy and use rice seeds.